2022
DOI: 10.1080/23311916.2022.2143051
|View full text |Cite
|
Sign up to set email alerts
|

Application of hybrid machine learning models and data pre-processing to predict water level of watersheds: Recent trends and future perspective

Abstract: The community's well-being and economic livelihoods are heavily influenced by the water level of watersheds. The changes in water levels directly affect the circulation processes of lakes and rivers that control water mixing and bottom sediment resuspension, further affecting water quality and aquatic ecosystems. Thus, these considerations have made the water level monitoring process essential to save the environment. Machine learning hybrid models are emerging robust tools that are successfully applied for wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 115 publications
(138 reference statements)
0
4
0
Order By: Relevance
“…It is 118 also hypothesized that the more objects participate in the sum, the smaller the relative approximation error will be. To test this hypothesis, modeling was carried out with the number of object models equal to three and four [34]. Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…It is 118 also hypothesized that the more objects participate in the sum, the smaller the relative approximation error will be. To test this hypothesis, modeling was carried out with the number of object models equal to three and four [34]. Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…This study focuses on the upstream area of the Three Gorges Reservoir, an essential part of the Yangtze River Basin, which is crucial for water resource management and flood control [30]. This study aims to select the best water-level-prediction algorithm among LSTM, BiLSTM, CNN-LSTM, and CNN-Attention-LSTM hybrid models [31]. By analyzing the predictive performance of each model in depth, the study aims to select the best waterlevel-prediction algorithm to improve prediction accuracy, thereby providing a scientific basis for reservoir operation management, flood warnings, and the rational allocation of water resources.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, articles on watershed-level predictions published between 2014 and 2021 were analysed by Mohammed et al [18]. Te study revealed that hybrid strategies outperform single methods for all cases, for instance, Ebtehaj et al [19], Imran et al [20], and Nguyen et al [21].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, knowledge gaps and promising new research directions of study related to the hybridisation of hybrid models need to be investigated. Also, Mohammed et al [18] reviewed the watershed-level prediction articles published from 2014 to 2021 and recommended employing all three data preprocessing approaches to improve original data quality and select the optimal predictors. Additionally, SSA is used for denoising data.…”
Section: Introductionmentioning
confidence: 99%